2010
DOI: 10.1111/j.1542-4758.2009.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of dialysis on mortality in critically ill, septic patients with acute renal failure

Abstract: Acute renal failure with concomitant sepsis in the intensive care unit is associated with significant mortality. The purpose of this study was to determine if the timing of initiation of renal replacement therapy (RRT) in septic patients had an effect on the 28-day mortality. Retrospective data on medical intensive care unit patients with sepsis and acute renal failure requiring RRT were included. Renal replacement therapy started with a blood urea nitrogen (BUN) of <100 mg/dL was defined as "early" initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 37 publications
1
64
2
5
Order By: Relevance
“…However, there was no significant difference in the recovery of kidney function by the timing of the initiation of dialysis. Similar results were obtained in a recent cohort study [193]. In a large-scale cohort study of critically ill patients with severe AKI in whom RRT was initiated on the basis of BUN and SCr levels, there was no significant difference in mortality between patients undergoing early (BUN \67.76 mg/dL) and late (BUN C67.76 mg/dL) RRT, and late RRT was associated with a longer duration of RRT [194].…”
Section: Level Of Evidence: I Grade Of Recommendation: B Rationale Cqsupporting
confidence: 73%
“…However, there was no significant difference in the recovery of kidney function by the timing of the initiation of dialysis. Similar results were obtained in a recent cohort study [193]. In a large-scale cohort study of critically ill patients with severe AKI in whom RRT was initiated on the basis of BUN and SCr levels, there was no significant difference in mortality between patients undergoing early (BUN \67.76 mg/dL) and late (BUN C67.76 mg/dL) RRT, and late RRT was associated with a longer duration of RRT [194].…”
Section: Level Of Evidence: I Grade Of Recommendation: B Rationale Cqsupporting
confidence: 73%
“…[28][29][30][31] This last practice may have been influenced by recent studies suggesting that starting dialysis earlier may improve prognosis. 29,[32][33][34][35] Unfortunately, despite the trends in increasing use of dialysis and starting it earlier, survival has remained poor. Unchanging mortality and rates of chronic dialysis also suggest these trends re flect a lower threshold for starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Carl et al 25 reported only 24.6% 1-year survival in a septic study population with AKI. The in-hospital mortality was reported as 38%-69% in a recent review, 26 which matches with our result of ∌60%.…”
Section: Discussion Survivalmentioning
confidence: 91%